PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD TERHADAP HASIL BELAJAR IPA KELAS IV SD NEGERI BANGUN REJO - Amelia, Bella; Lokaria, Eka; Yuneti, Armi (LP4MK STKIP PGRI Lubuklinggau, 2024)
This research aims to determine the completeness of the science learning outcomes of grade IV students at Bangun Rejo State Elementary School, after implementing the STAD Type Cooperative learning model. The method used in this research was quasi-experimental and the research subjects were class IV of SD Negeri Bangun Rejo. The instrument used is multiple choice test questions. The research results show that the average Pre-Test score is 51.92. After being treated using the STAD Type Cooperative learning model, the post-test result was 77.27. If the hypothesis Z_count Z_table is 2.53, then this result can also be compared with Z_table at the 5% significance level, namely: 2.53> 2.03. then H_oditolak H_adiwas accepted after applying the STAD Type Cooperative model to the science learning outcomes of class IV students at SD Negeri Bangun Rejo which was declared complete. Keywords: Science learning outcomes, STAD Type Cooperative